The Pengaruh Audit Operasional Pada Efektivitas Penjualan SSL - Chrestella, Amadea; Setiawan, Santy (Universitas Katolik Indonesia Atma Jaya, 2024)
The purpose of this research is to assess whether SSL's operational audit has been implemented properly, whether SSL's sales targets have been achieved, and whether SSL's operational audit has played a role in supporting the achievement of sales effectiveness. Sales activities are the primary focus of SSL’s operations, with a key objective of increasing sales volume as it directly impacts the company’s profitability. Profitability is vital for business continuity, necessitating the effective functioning of salles activities. Therefore, the role of operational audit is needed to assess the functioning of sales activities. The research employs a causal and descriptive methodology, with the dependent variable being the achievement of sales effectiveness and the independent variable being the operational audit. Data for this study were obtained through direct observation, interviews, questionnaires, as well as documents and written reports. The findings indicate that the operational audit has been implemented properly, SSL's sales targets have been achieved, and there is an influence of the operational audit on the attainment of sales effectiveness.